2007
DOI: 10.17221/753-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Screening of antimicrobial activity of essential oil and methanol extract of Satureja hortensis on foodborne bacteria and fungi

Abstract: The present work reports the <i>in vitro</i> antimicrobial activities of the essential oil and methanol extract from <i>Satureja hortensis</i> as well as the content of its essential oil. The chemical composition of hydrodistilled essential oil of Satureja hortensis was analysed by means of GC-MS. Thirty constituents were identified. The main constituents of the oil were thymol (40.54%), &gamma;-terpinene (18.56%), carvacrol (13.98%), and <i>p</i>-cymene (8.97). The esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 45 publications
5
67
3
Order By: Relevance
“…our results indicate that S. hortensis essential oil, collected in Serbia, showed higher activity in relation to the results from previous studies (1,6,8,25). Activity against B. subtilis of this oil was in the range from MIC/MBC=0.39/0.78 μl/ml, while the oil collected from Yusufeli in turkey did not show any effect against this strain.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…our results indicate that S. hortensis essential oil, collected in Serbia, showed higher activity in relation to the results from previous studies (1,6,8,25). Activity against B. subtilis of this oil was in the range from MIC/MBC=0.39/0.78 μl/ml, while the oil collected from Yusufeli in turkey did not show any effect against this strain.…”
Section: Resultssupporting
confidence: 65%
“…In the present paper, the oil exhibited very high antifungal activity against A. niger (Mic/MBc=0.78 μl/ml), S. cerevisiae (MIC/MBC=0.39/0.20 μl/ml) and C. albicans (MIC/MBC=0.20 μl/ml). Against C. albicans, the oil from turkey did not show any effect (1). According to this, savory oil can be considered as a potential natural agent for the treatment of candidiasis.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…S. hortensis essential oil was active against E. coli O157:H7, S. typhimurium, S. aureus and L. monocytogenes in the range from 0.013-0.003 μl/ml, as well as against Pseudomonas putida strain isolated from meat with a MIC of 0.05% and a MTC of 0.013% [13]. The oil showed activity against 25 (of 32 species) bacteria in the range from 15.62 -250 μl/ml and against 3 (of 10) fungal strains in the range from 62.5 -125 μl/ml [14]. The essential oil of summer savory (Satureja hortensis L.) inhibited the mycelial growth of phytopathogenic fungi Alternaria mali and Botrytis cinerea, and exhibited a fungicidal effect [7].…”
Section: Antimicrobial Activity Of S Hortensis Essential Oilmentioning
confidence: 98%
“…Several studies have been performed concerning the antimicrobial activity of essential oils or extracts of other Satureja species [3]. Many of the previous studies demonstrated that the members of the genus Satureja show a high antimicrobial activity due to the presence of thymol, carvacrol and their precursors [21][22][23]. In conclusion, it can be suggested that S. bachtiarica extract in "in vitro" have considerable antimicrobial ability against the studied strains.…”
Section: Discussionmentioning
confidence: 98%